2007
DOI: 10.1002/cncr.22532
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus oxaliplatin (GEMOX) in patients with advanced hepatocellular carcinoma (HCC)

Abstract: BACKGROUND. New systemic therapies are needed to improve the prognosis of patients with advanced-stage hepatocellular carcinoma (HCC). In a Phase II trial involving previously untreated patients with advanced HCC, the more favorable schedule from a previous pilot study was evaluated. METHODS.Thirty-four patients with previously untreated advanced-stage HCC were prospectively enrolled. The GEMOX regimen consisted of gemcitabine 1000 mg/m 2 on Day 1 and oxaliplatin 100 mg/m 2 on Day 2. The treatment was repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(126 citation statements)
references
References 44 publications
7
115
0
4
Order By: Relevance
“…Many small-scale trials of combining MTT with cytotoxic chemotherapy have been reported [385][386][387][388][389]. However, the treatment efficacy in terms of tumor response rate and patient survival were similar to those reported for the cytotoxic regimens alone (Table 3) [372,[375][376][377][378][379][380][381][382]. A second approach is to combine MTT targeting different molecular pathways.…”
Section: Future Directionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Many small-scale trials of combining MTT with cytotoxic chemotherapy have been reported [385][386][387][388][389]. However, the treatment efficacy in terms of tumor response rate and patient survival were similar to those reported for the cytotoxic regimens alone (Table 3) [372,[375][376][377][378][379][380][381][382]. A second approach is to combine MTT targeting different molecular pathways.…”
Section: Future Directionsmentioning
confidence: 84%
“…The most common grade 3-4 toxicity was myelosuppression, which occurred in 10-40% of the patients. Combination regimens, such as cisplatin/IFN/doxorubicin/ fluorouracil (PIAF), gemcitabine/oxaliplatin (GEMOX), or capecitabine/oxaliplatin (XELOX), can increase the objective response rate to approximately 20% but at the expense of increased treatment-related toxicities [382,383]. Therefore, cytotoxic chemotherapy can be used with caution only in selected patients with advanced HCC.…”
Section: Cytotoxic Therapy: Single Agent and Combinationmentioning
confidence: 99%
“…Although GEMOX was well-tolerable with the most common grade 3/4 toxicities of thrombocytopenia (27%) and neutropenia (24%) in patients with advanced HCC, the clinical outcome was not impressive with ORR of 18% (n=6) in a phase II study (44). Interestingly, all the objective responses were observed in patients with nonalcoholic underlying liver disease (6/21) but not with alcoholic liver disease (0/13).…”
Section: Gemcitabine Based Combination Chemotherapymentioning
confidence: 98%
“…The gemcitabine plus oxaliplatin (GEMOX) regimen appeared to be the most promising, based on its lack of renal and hepatic toxicity in patients with underlying cirrhosis and its interesting efficacy in phase II trials [95][96][97] . The largest multicenter study suggested that GEMOX is effective with an acceptable profile of safety; the induced tumor response allowed a secondary local therapy option that was not initially feasible in a significant proportion of patients, which suggests that it could be indicated as a first line treatment for patients who may particularly benefit from tumor downsizing [2] .…”
Section: Chemotherapymentioning
confidence: 99%